2) (4n + 3n) · 11 = 154: 3) 45 : (4m - m) = 3;
4) (19n – 6n): 4 = 26;
5) (16m + 5m): 18 = 7;
6) (17n - 8n) · 13 = 351.
110. 1) (12m - 5m) · 4 = 252;​

SeverBig36 SeverBig36    1   15.09.2020 06:23    1

Ответы
zenkov2000cemen zenkov2000cemen  15.10.2020 21:42

Пошаговое объяснение:


2) (4n + 3n) · 11 = 154: 3) 45 : (4m - m) = 3;4) (19n – 6n): 4 = 26;5) (16m + 5m): 18 = 7;6) (17n -
2) (4n + 3n) · 11 = 154: 3) 45 : (4m - m) = 3;4) (19n – 6n): 4 = 26;5) (16m + 5m): 18 = 7;6) (17n -
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика